Faktor Internal dan Eksternal dengan Tingkat Stres pada Mahasiswa Keperawatan - D. hukom, Sridina; Suhermi; Alam, Rizqy Iftitah (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Students who experience stress can have a positive or negative impact. An increase in the amount of academic stress will reduce academic ability which affects the achievement index. Even those that are considered too heavy can trigger memory problems, concentration, decreased problem-solving abilities, and academic abilities. This study aims to determine the influence of external and internal factors on stress levels in fourth semester nursing students. This type of research is an analytic survey research, which is to identify the influence of internal and external factors on stress levels on nursing students. The research design used is a cooperative research design (cross sectional). The sample in this study was all prigravida maternity mothers with a total of 54 respondents. The relationship test was carried out using the Regression test with a significance level (Î±) of 0.05. Regression test results p = 0.000, which means the p value is smaller than the value (Î±) 0.05, thus H0 is rejected and Ha is accepted. Interpretation of the influence of internal and external factors on stress levels in fourth semester nursing students. With this study, it can be concluded, UMI nursing students in semester IV at the Indonesian Muslim University, where students who experience stress caused by internal factors get 27 students (i) (50.0%) who experience severe stress levels, while 17 students (i) (31.5%) who experienced moderate stress. internal factors obtained 29 students (i) (53.7%) who experienced severe stress levels, while 17 students (i) (31.5%) experienced moderate stress.